Horizontal and Vertical Position of the Mental Foramen on Panoramic Views of a Selected Iraqi Population (Mustansiria Dental Journal, 2018)
The mental foramen is the opening of the short mental canal, through which themental nerve the terminal branch of the inferior alveolar nerve exits, knowing theexact position of the mental foramen is essential in oral surgical procedures. Thisstudy determines this position in a selected Iraqi population.240 panoramic radiographs of Iraqi population selected from three different oraland maxillofacial centers to identify the normal range of position of the mentalforamen, both horizontal and vertical position were studied, radiographs with anyerrors or taken for patients not co inside with our criteria were excluded.In horizontal position , 51.31% were found apical to the lower second premolar ,43.64% between the first and second premolars, 3.07% were found between secondpremolar and lower first molar, 1.09% were found apical to the lower first premolar,0.87% were found between lower canine and lower first premolar.In vertical position,60.08% were found inferior to the apex of the related tooth,36.84% were found within the apex of the related tooth while 3.07% were foundsuperior to the apex.The mental foramen can be found anywhere from lower canine to the lower firstmolar, although 94.95% of the studied radiographs showed that mental foramen waslocated either between the lower premolars or at the apex of the second premolar.